A Single-Factor Consumption-Based Asset Pricing Model. (14th September 2018) - Delikouras, Stefanos; Kostakis, Alexandros
Abstract : We propose a single-factor asset pricing model based on an indicator function of consumption growth being less than its endogenous certainty equivalent. This certainty equivalent is derived from generalized disappointment-aversion preferences, and it is located approximately 1 standard deviation below the conditional mean of consumption growth. Our single-factor model can explain the cross section of expected returns for size, value, reversal, profitability, and investment portfolios at least as well as the Fama–French multifactor models. Our results show strong empirical support for asymmetric preferences and question the effectiveness of the smooth utility framework, which is traditionally used in consumption-based asset pricing.